INTEGRASI PEMBELAJARAN PAI MELALUI MATA PELAJARAN IPA DALAM UPAYA MENINGKATKAN KOMITMEN KEAGAMAAN SISWA SMA PRIMAGANDA JOMBANG - Sugiyanto Sugiyanto; lmron Arifin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
This study aims to analyze the Integration Efforts of Islamic Religious Education Learning Through Natural Science Subjects in an Effort to Increase Students' Religious Commitment. This study uses a qualitative approach. Data collection was done by interview, observation and documentation. This study found that: (1) Efforts to integrate science and PAI learning are pursued through the example of school principals and teachers, translation of the school's vision and mission, as well as the implementation of learning programs with Islamic values. 2) Implementation of integrated natural science learning with Islamic values is carried out with strategies, namely: always mentioning the name of Allah, using terms, applications or examples, and inserting relevant verses or hadiths. 3). There are four contributions to the integration of science and PAI learning in increasing students' religious commitment, namely contributions in the fields of moral aqidah, quran hadith, fiqh, and history of Islamic culture.